Paradigm Shifts in Early and Modern Chinese Religion: A History - Lagerwey, John (Handbook of Oriental Studies. Section 4 China Ser, 2018)
Intro -- Contents -- Preface -- Preliminaries -- Chapter 1 Intellectual Change in the Warring States and Han (481 BC-220 AD) -- 1 Paradigm Shift in the Warring States -- 2 The Attack on Shamanism -- 3 The Emergence of Self-Cultivation Practice -- 4 The Philosophical Preparation of Political Unity -- 5 Han Religion -- 6 Changing Theories of Illness -- Chapter 2 Religious Transformation in the Period of Division (220-589 AD) -- 1 The Three Teachings and Shamanism -- 2 Religious Communities -- 3 Rituals -- 4 Scriptures -- 5 Literature -- 6 Sacred Geography -- 7 Popular Religion -- Chapter 3 Religion and Thought in the Song, Jin, and Yuan (960-1368) -- 1 "Modern China" -- 2 State Religion -- 3 Local Society -- 4 Daoism in the Song and Jin -- 5 Buddhism in the Song -- 6 Confucianism in the Song -- Chapter 4 Structuring Values 1850-2015 -- 1 Religion and Modernity -- 2 Economics -- 3 Science and Scientism -- 4 Gender -- 5 Spirit Writing, Redemptive Societies, and Charity Halls -- 6 Charismatic Christianity -- By Way of Conclusion -- Bibliography of Chapters Cited -- Index